Answer: -5/4
Step-by-step explanation:
Apply the fraction rule: a/-b = -a/b
-5/6/2/3
-----------------------------------------------------------------------------------------------------------------
Divide fractions: a/b/c/d = a x d/ b x c
-5 x 3 / 6 x 2
-----------------------------------------------------------------------------------------------------------------
Multiply the numbers: 6 x 2 = 12
-5 x 3 / 12
-----------------------------------------------------------------------------------------------------------------
Multiply the numbers: 5 x 3 = 15
-15/12
-----------------------------------------------------------------------------------------------------------------
Cancel the common factor.3
-5/4
-----------------------------------------------------------------------------------------------------------------
Sorry if this is a little confusing but your answer to the question is ( -5/4 )
Answer:
x = 14
Step-by-step explanation:
Step 1: First, Simplify the fraction.
![\frac{4x}{7} =8](https://tex.z-dn.net/?f=%5Cfrac%7B4x%7D%7B7%7D%20%3D8)
Step 2: Next, Multiply both sides by 7.
4x = 8 × 7
Step 3: Simplify 8 × 7 to 56.
4x = 56
Step 4: Then, Divide both sides by 4.
![x=\frac{56}{7}](https://tex.z-dn.net/?f=x%3D%5Cfrac%7B56%7D%7B7%7D)
Step 5: Lastly, Simplify the fraction and you're done!
x = 14
Answer:
My Answer: <u>33.95</u>
Step-by-step explanation:
x - 13.75 = 20.2
so because it is subtracting we have to add.
x - 13.75 + 13.75 = 20.2 + 13.75
when added, x will cancel out, and we will be left with the answer.
x = 33.95
GL!
-Oceaniii
Answer:
The direction of mathematics teacher is study about the mathematics teacher is study about it is by step instructions
Answer:
f^(-1)(x) = \frac{-1}{5} (x+4)
Step-by-step explanation:
Given is a function
![f(x) = -5x-4\\](https://tex.z-dn.net/?f=f%28x%29%20%3D%20-5x-4%5C%5C)
To find its inverse.
We must check whether f is one to one or onto first
If -5x1-4 = -5x2-4 we get x1=x2
Hence f is one to one
Also for every f(x) we can find a x so f is onto.
So inverse exists
Let
![y=-5x-4\\-5x=y+4\\x=\frac{-1}{5} (y+4)](https://tex.z-dn.net/?f=y%3D-5x-4%5C%5C-5x%3Dy%2B4%5C%5Cx%3D%5Cfrac%7B-1%7D%7B5%7D%20%28y%2B4%29)
Replace x by f inverse and y by x
![f^(-1)(x) = \frac{-1}{5} (x+4)](https://tex.z-dn.net/?f=f%5E%28-1%29%28x%29%20%3D%20%5Cfrac%7B-1%7D%7B5%7D%20%28x%2B4%29)